A Sustainable Biosphere Through Intelligent Technologies - Nath, Shuvrajit; Banerjee, Ranjan; Nayak, Partha Shankar; Mitra, Shankar Prasad; Mukherjee, Debmalya (Journal of Neonatal Surgery, 2025)
This chapter investigates the revolutionary capacity of artificial intelligence (AI) to support a resilient and enduring biosphere. It examines how AI technologies, encompassing machine learning, deep learning, and computer vision, can fundamentally change the way we approach biodiversity protection, ecological observation, and the creation of environmentally friendly bio-based solutions. Key areas of focus include AI-driven identification and monitoring of species, predictive modelling of ecological disruptions, precision agriculture methods for improved resource management, and the development of innovative biomaterials and biofuels through AI-powered drug discovery and bioengineering. Furthermore, the ethical implications and potential difficulties linked to AI-based environmental stewardship are critically analyzed, covering topics such as data security, algorithmic prejudice, and the accountable implementation of autonomous systems. This research aims to deliver a thorough analysis of the opportunities and challenges presented by AI in establishing a more sustainable and robust biosphere for generations to come.